A Validated Method for Quantifying Entecavir in Biological Matrices and Its Application in a Pharmacokinetic Study in Rats and Dogs - Huang, X.; Jiang, Z.-Z.; Tang, W.-W.; Xiao, Y.; Zhang, L.-Y.; Zhang, Z.-J. (Drug Research, 2013)
A sensitive and specific liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS) method that uses ganciclovir as an internal standard (IS) has been developed and validated for quantifying entecavir in rat and dog plasma. Following solid-phase extraction (SPE), the analytes were separated on an Inertsil® ODS-3 (5 μm, 150 mm×2.1 mm i.d.) column and analyzed in selected ion monitoring (SIM) mode with a positive electrospray ionization (ESI) source using the [M+H]+ ions, 278.1 for entecavir and 256.0 for ganciclovir. The method was validated over the concentration range of 0.01–9 μg/mL for entecavir. All precisions (RSD) within and between batches were less than 10%, and accuracies ranged from 98.1 to 102.5%. The lower limit of quantification was 0.01 µg/mL. The extraction recovery averaged 93.9–96.7%. The validated method was used for a pharmacokinetic study of entecavir in rats and dogs. The following pharmacokinetic parameters were obtained for rats and dogs, respectively: the area under the plasma concentration vs. time curves from time 0 to 24 h (AUC0–24) were 15.4±4.5 and 23.4±7.2 μg∙h/mL; the mean maximum plasma concentration (Cmax) were 2.4±0.8 and 5.0±0.9 μg/mL; the mean time to reach the maximum plasma concentrations (Tmax) were 1.7±0.7 and 1.5±0.4 h; and the mean elimination half-life (t1/2) were 5.3±1.4 and 3.8±1.3 h.
Keywords: entecavir; pharmacokinetics; LC/MS; rat; dog